2022
DOI: 10.1002/cpt.2571
|View full text |Cite
|
Sign up to set email alerts
|

The Polymorphic Nuclear Factor NFIB Regulates Hepatic CYP2D6 Expression and Influences Risperidone Metabolism in Psychiatric Patients

Abstract: The genetic background for interindividual variability of the polymorphic CYP2D6 enzyme activity remains incompletely understood and the role of NFIB genetic polymorphism for this variability was evaluated in this translational study. We investigated the effect of NFIB expression in vitro using 3D liver spheroids, Huh7 cells, and the influence of the NFIB polymorphism on metabolism of risperidone in patients in vivo. We found that NFIB regulates several important pharmacogenes, including CYP2D6. NFIB inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
2
23
1
Order By: Relevance
“…Furthermore, rs35107470 was shown the be associated with metabolism of caffeine, which is a CYP1A2 substrate 21 . In line with our recent study, we did not observe other genetic variants that are in linkage disequilibrium with the NFIB‐C variant 31 …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, rs35107470 was shown the be associated with metabolism of caffeine, which is a CYP1A2 substrate 21 . In line with our recent study, we did not observe other genetic variants that are in linkage disequilibrium with the NFIB‐C variant 31 …”
Section: Resultssupporting
confidence: 90%
“… 21 In line with our recent study, we did not observe other genetic variants that are in linkage disequilibrium with the NFIB‐C variant. 31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study showed that NFIB rs28379954 T>C carriers that were also CYP2D6 extensive metabolizers had comparable CYP2D6 activity to ultrarapid metabolizers. This highlights that NFIB polymorphisms are important to consider in CYP2D6 drug metabolism 31 …”
Section: Resultsmentioning
confidence: 97%
“…CPIC guideline recommends alternative analgesics to the two prodrugs, codeine (number 7) and tramadol (number 21), in poor metabolizers or ultrarapid metabolizers, 29 as they are more likely to experience poor pain relief or more adverse effects compared to intermediate metabolizers and extensive metabolizers 30 . The nuclear factor 1B (NFIB) was recently discovered to regulate CYP2D6 gene expression in vitro 31 . The same study showed that NFIB rs28379954 T>C carriers that were also CYP2D6 extensive metabolizers had comparable CYP2D6 activity to ultrarapid metabolizers.…”
Section: Resultsmentioning
confidence: 99%